Cranial base influence on the nasomaxillary complex in Class II division 1 malocclusion (Three dimensional cephalometric study) - Khidair A Salman; Mustafa M Hamed (University of Mosul, College of Dentistry, 2006)
Aim: To evaluate the effect of the cranial base on the nasomaxillary complex in class II division 1 malocclusion. Materials and Methods: The study was carried out on a sample of 104 Iraqi subjects in Mosul City aged 18-24 years 53 females and 51 males having class II division 1 malocclusion. Lateral and posteroanterior radiographs were taken for each subject and twenty three measurements were used (Nine angular and fourteen linear). Results of the analysis were the median (NSBa), lateral cranial base (NSCo) and saddle angle (NSAr) showed a significant effect on the inclination of the Frankfort plane from the anterior and posterior cranial base in same direction, For the saddle angle significantly affect the inclination of the Frankfort plane but in the opposite direction while on anteroposterior position of alveolar process of the premaxilla (SNPr) in the same direction. The anterior part (SN), second lateral posterior part (SCo) and depth of cranial base (NBa) significantly affect the maxillary length (ApMax-PNS), upper anterior (N-ANS) and posterior facial height (S-PNS). For the median posterior part (SBa) and first lateral posterior part (SAr) no significant effect on (upper anterior facial height). The anterior cranial base width (GL-GL) showed a significant affect [facial (Zy-Zy), maxillary (J-J) and upper intermolar width (U6-U6)]. While posterior cranial base width (Mas-Mas) was significantly affect [facial (Zy-Zy), maxillary (J-J) and nasal width (Nc-Nc)].Conclusion: The median, lateral cranial base and saddle angles showed correlation with the inclination of the Frankfort plane from the anterior and posterior cranial base. The observed impact of the cranial base widths on the nasomaxillary complex widths were for anterior cranial base width there was a significant effect on bizygomatic, bimaxillary and intermolar width